Exosomes From Astrocyte Processes: Signaling to Neurons - Venturini, Arianna; Passalacqua, Mario; Pelassa, Simone; Pastorino, Fabio; Tedesco, Mariateresa; Cortese, Katia; Gagliani, Maria Cristina; Leo, Giuseppina; Maura, Guido; Guidolin, Diego; Agnati, Luigi F.; Marcoli, Manuela; et al. (Frontiers in Pharmacology, 2019)
It is widely recognized that extracellular vesicles subserve non-classical signal transmission in the central nervous system. Here we assess if the astrocyte processes, that are recognized to play crucial roles in intercellular communication at the synapses and in neuron-astrocyte networks, could convey messages through extracellular vesicles. Our findings indicate, for the first time that freshly isolated astrocyte processes prepared from adult rat cerebral cortex, can indeed participate to signal transmission in central nervous system by releasing exosomes that by volume transmission might target near or long-distance sites. It is noteworthy that the exosomes released from the astrocyte processes proved ability to selectively target neurons. The astrocyte-derived exosomes were proven positive for neuroglobin, a protein functioning as neuroprotectant against cell insult; the possibility that exosomes might transfer neuroglobin to neurons would add a mechanism to the potential astrocytic neuroprotectant activity. Notably, the exosomes released from the processes of astrocytes maintained markers, which prove their parental astrocytic origin. This potentially allows the assessment of the cellular origin of exosomes that might be recovered from body fluids.